Transparent vertical nanotube electrode arrays on graphene for cellular recording and optical imaging - Jamin Lee; Keundong Lee; Kyumeen Kang; Asad Ali; Dong Wook Kim; Hyerim Ahn; Gwanho Ko; Myunghwan Choi; Youngbin Tchoe; Hye Yoon Park; Gyu-Chul Yi (NPG Asia Materials)
Abstract Here, we report the fabrication of transparent multichannel vertical nanotube electrode arrays for detecting cellular activity and optically imaging neuronal networks. To fabricate these transparent electrode arrays, position- and morphology-controlled ZnO nanotube arrays consisting of ultrathin nanowalls were grown on transparent graphene layers and coated with Ti/Au metal layers. Using these multichannel arrays, electrophysiological signals were individually recorded from primary mouse hippocampal neurons and recorded distinctive intracellular potential-like signals. Moreover, the transparent electrode array enabled fluorescence imaging of neuron cell bodies and neurite connections. This transparent graphene- and nanotube-based recording device is proposed to greatly increase the versatility of capabilities for investigating neuronal activity through simultaneous recording and imaging of neuron cultures.